Pengaruh Variasi JarakKolom Kapur dalam Stabilisasi Tanah Lempung Lunak pada Tinjauan Nilai Indek Pemampatan Tanah(Cc) - Arwan Apriyono; Sumiyanto Sumiyanto (Dinamika Rekayasa, 2011)
Numerousbuildingslocated in north area of Java Island encountersettlement problem. The settlementoccurs because most ofsoil in the areais soft clay soil. The behavior of this soilis characterized by the large value of coefficient compression (Cc) and small valueof bearing capacity. This condition causes potentially great consolidation settlement. In this research, limes column stabilization method will be applied to make soft clay soil better. Limes columns were expected to reduce Cc value therefore consolidation settlement decreases. This research was conducted throughlaboratory experiment, usingbox100 cm in lengths, 40 cm in wide, and 40 cmin height. Three variations of diameters (5 cm, 10 cm, 15 cm) and three variations of distance of sample taken from outside of the limes column mould (10 cm,20 cm, 30 cm) was applied in this research. Influence of limes column to the value of Ccwasexamined. The result of this research showsthat limescolumn couldsignificantlyreduceCcvalue. TheCc valuedecreases when thedistance of sample taking placedecreases. The average of Ccdeclineon three variationsdistance of column (10 cm, 20 cm, 30 cm)are 17.28%, 44.97%, 52.24%respectively. The most efficient distance of thelimes column is 20 cm.